La influencia del blues y el jazz en tres autoras afro-estadounidenses: Toni Morrison, Alice Walker y Gayl Jones - Cobo Piñero, María Rocío (2014)
This Thesis approaches blues and jazz from a multiple perspective: as literary themes, as transgressive rhythms, as sites of vindication and as symbols of the music that emerged from the cultural contact during the diaspora. We explore the influence of these musical genres in three literary works written by each of the following authors: Toni Morrison, Alice Walker and Gayl Jones. These texts, mainly published between the 1970s and the beginning of the 1980s, show the influence of the musical legacy of the female blues singers, the syncopated rhythms of jazz and the vernacular culture of US African descendants. Female black writers break with the literary tradition of connecting just male authors with blues and jazz, leading the black female literary renaissance of the 1970s. This investigation brings together black feminist criticism, literary studies, and the history of black music to establish the role of blues and jazz as a means of resistance to race, class, and gender inequalities; the latter was pointed out by the female blues singers first and by the authors analyzed in this Thesis afterwards. The connection between the social background of music and the historical time in which the literary texts are settled is highly emphasized in this study.